Modulation of Plasma Proteomic Profile by Regular Training in Male and Female Basketball Players: A Preliminary Study - Militello, Rosamaria; Pinto, Gabriella; Illiano, Anna; Luti, Simone; Magherini, Francesca; Amoresano, Angela; Modesti, Pietro Amedeo; Modesti, Alessandra (Frontiers in Physiology, 2022)
Monitoring of fatigue and recovery during training periods contribute to identify the best training method to achieve sports performance. To date little is known about sex-related differences in sport adaptations. Aim of the present study is to identify sex-related sport adaptation proteins in female and male basketball players using proteomics approach on plasma samples withdraw from athletes during in-season training period but far from a competition. A cohort of 20 professional basketball players, 10 females (BF) and 10 males (BM), and 20 sedentary males (10 CM) and females (10 CF) as control, of comparable age and BMI were involved in this study. Protein profiles of plasma samples obtained from BM, BF, CM and CF were analysed by 2-DE. Differentially expressed proteins were identified by mass spectrometry. The computational 2-DE gel image analysis pointed out 33 differentially expressed protein spots (ANOVA p-value<0.05) and differences between male and female are more evident among the players than controls. The expression profile of 54.5% of the total proteins is affected by the sport activity. 14 proteins are differentially expressed in basket female players in comparison with their relative controls while 7 are differentially expressed in basket male players in comparison with their controls. In conclusion, we identify in female athletes a reduction in proteins related to transcription regulation, most of these modulate chronic inflammation confirming the anti-inflammatory effect of regular training in female muscle metabolism. In male and female athletes, we found a decrease in Transthyretin involved in muscle homeostasis and regeneration and Dermcidin a stress-induced myokine linked to inflammatory and it will be interesting to fully understand the role of its different isoforms in male and female skeletal muscle contraction.